Cause-specific excess mortality in patients treated for cancer of the oral cavity and oropharynx: A population-based study. (January 2016) - van Monsjou, H.S.; Schaapveld, M.; Hamming-Vrieze, O.; de Boer, J.P.; van den Brekel, M.W.M.; Balm, A.J.M.
Highlights: We assessed cause-specific mortality in a population-based cohort of 14, 393 patients treated for OC/OPSCC. The main cause of death remains death due to cancer of the head and neck. OC/OPSCC patients have significant excess mortality due to SPT outside the HN, cardiovascular and gastrointestinal diseases. Excessive alcohol and tobacco causes most of the excess mortality, they should be controlled. OPSCC patients experienced a more than 2 times higher risk of death due to pneumonia than OCSCC patients. Summary: Purpose: To assess cause-specific mortality in a large population-based cohort of 14, 393 patients treated for squamous cell carcinoma of the oral cavity (OC) or oropharynx (OP) in The Netherlands between 1989 and 2006. Patients and methods: Causes of death were obtained for 94.7% of 9620 patients who had died up to January 1, 2009. We assessed standardized mortality ratios (SMR) and absolute excess mortality (AEM), comparing observed cause-specific mortality with expected mortality for our cohort based on general population mortality rates. Results: Median survival was 3.9 years. Overall, the study population experienced a 6-fold higher (95% Confidence Interval (95% CI) 5.9–6.1) mortality risk compared with the general population. After three years, 41% of OP and 29% of OC patients had died due to cancer of the oral cavity and pharynx. Additionally, OC and OP patients experienced high excess mortality from esophageal (SMR 10.6 and 17.9) and lung cancer (SMR 4.6 and 6.3). With regard to non-cancer deaths, the highest AEMs were due to diseases of the circulatory system, with OC patients experiencing an AEM of 11.3 per 10, 000 person-years for ischemic heart disease. OP patients experienced excess mortality due to pneumonia (AEM 22.1 per 10, 000 person-years). The risk of death due to diseases of the digestive system was for OP and OC patients where about equal (AEM 28.7 and 23.80, respectively). The SMR for death due to pneumonia was more than two times higher (4.4 vs. 1.7) for OP patients than for OC patients ( P  < 0.001). From 15 years after diagnosis, second tumors located outside the head and neck region accounted for most of the excess mortality. Conclusions: Excess mortality in OC and OP patients appears to be dominated by effects of heavy tobacco and alcohol use with high AEM due to second tumors, respiratory, cardiovascular and gastrointestinal diseases. Patients with OP experienced more than two times higher risk of death due to pneumonia than OC patients. Therefore, awareness of this potential complication should be raised along with development of prevention strategies.